STRATEGI INFECTION PREVENTION CONTROL NURSE (IPCN) MEMINIMALISASI KEJADIAN TERTUSUK JARUM SUNTIK PADA PERAWAT RAWAT INAP DI RSU MITRA SEJATI MEDAN TAHUN 2020 - HESTY HERLINA OMPUSUNGGU (Jurnal Kajian Kesehatan Masyarakat, 2020)
STRATEGY INFECTION PREVENTION CONTROL NURSE TO MINIMIZE THE INCIDENCE OF NEEDLE STICKING TO NURSES IN THE IN PATIENT HOSPITAL OF MITRA SEJATI MEDAN IN 2020 Hesty Herlina Ompusunggu 1, Elisabeth Dame Manalu 2, Herri Novita Tarigan3 Email : hestyherlina@gmail.com 1Masters Program Faculty Alumni of Public Health Institute of DELI HUSADA Deli Tua 2Lecture of Public Health Institute of DELI HUSADA Deli Tua Mitra Sejati General Hospital is one of the Medan North Sumatra Private Hospitals which also has an important role in health services. In terms of improving work safety especially for nurses, Mitra Sejati Hospital has made several policies such as establishing Standard Procedures Operating (SPO) before and after taking action on patients. However, there were still find the incidents the of needle sticking to nurses in the Mitra Sejati General Hospital Medan. The purpose of this study was to determine the strategy "Infection Prevention Control Nurse (IPCN)" to minimize the incidence of needle sticking to nurses in the Inpatient Hospital of Mitra Sejati Medan in 2020. The type of this study was a qualitative descriptive design study that was presented exploratively. The informants in this study were 7 (seven) people, namely Nursing Supervisor, Head of Inpatient Room, Managing Nurse, Chairperson of PPI, Infection Prevention Control Nurse (IPCN). Data collection techniques in this study used in-depth interviews. The results showed that Mitra Sejati General Hospital already had a SPO on the use of Personal Protective Equipment (PPE), SPO of Safe Injection Practice, but the obstacles faced were still some nurses who did not attend the SPO. Likewise, related to health protection, officers are still not running optimally where health workers, especially nurses, have not received regular health checks. In the management of sharps waste namely syringes, syringes are still found misplaced, for example after taking action. The conclusion that can be concluded from this study is that the use of Personal Protective Equipment (PPE), SPO Safe Injecting Practices, Health protection for officers and management of sharps waste ie syringes have not been implemented optimally which causes the occurrence of needle sticking in nurses. Therefore, it is recommended for officers to carry out the SPO that has been set optimally and the Hospital leaders must make a policy so that staff health checks can be carried out regularly and a policy regarding written sanctions to officers is required. Who disobey no comply with the service SPO.